Respuesta :

Answer:

x=1, y=1, z=0

Step-by-step explanation:

System of Equations

We are required to solve the system of equations by elimination:

[tex]\left\{\begin{matrix}-2x+2y+3z=0\qquad [1]\\-2x-y+z=-3 \qquad [2]\\2x+3y+3z=5 \qquad [3]\end{matrix}\right[/tex]

Adding [1] and [3], and subtracting [1] and [2]:

[tex]\left\{\begin{matrix}5y+6z=5\qquad [4]\\3y+2z=3\qquad [5] \end{matrix}\right.[/tex]

Multiplying [5] by -3 and adding to [4]:

[tex]-4y=-4[/tex]

Solving:

[tex]y = -4 / (-4) = 1[/tex]

[tex]y=1[/tex]

Substituting into [5]:

[tex]5(1)+6z=5[/tex]

Simplifying:

[tex]6z = 0[/tex]

z=0

Substituting into [3]

[tex]2x+3(1)+3(0)=5[/tex]

Operating:

[tex]2x+3=5[/tex]

[tex]2x = 2[/tex]

[tex]x = 2/2=1[/tex]

x=1

The solution is

x=1, y=1, z=0